The Influence of Perceived Benefits, Perceptions of Ease and Perception of Risks on Student’s Cryptocurrency Investment Interest - Luh Gede Kusuma Dewi; Nyoman Trisna Herawati; Made Arie Wahyuni (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
This research aims to determine the effect of perceived benefits, perceived convenience and perceived risk on cryptocurrency investment interest in the province of Bali. The population of this research are all students in the province of Bali. The sampling method in this research used a non-probability sampling method with an accidental sampling approach. The results indicate that The Effect of Perceived Benefits (X1) has a significant effect on Cryptocurrency Investment Interest (Y); The Effect of Perceived Ease (X2) and The Effect of Investment Risk (X3) has no significant effect on Cryptocurrency Investment Interest (Y). Based on the results of the R-Square test, perceptions of benefits, perceptions of convenience, and investment risk affect interest in cryptocurrency investment by 21.9%, while the remaining 78.1% is influenced by other variables outside of this research. It is hoped that this research will be useful for the development of future research. Key words : perceived benefits; perception of convenience; risk perception; investment interest; cryptocurrency